Elastomeric Free-Form Blood Vessels for Interconnecting Organs on Chip Systems - Zhang, Weijia (Lab Chip, 2016)
Conventional blood vessel-on-a-chip models are typically based on microchannel-like structures enclosed within bulk elastomers such as polydimethylsiloxane (PDMS). However, these bulk vascular models largely function as individual platforms and exhibit limited flexibility particularly when used in conjunction with other organ modules. Oftentimes lengthy connectors and/or tubes are still needed to interface multiple chips, resulting in a large waste volume counterintuitive to the miniaturized nature of the organs-on-chips. In this work, we report the development of a novel form of vascular module based on PDMS hollow tubes, which closely emulates the morphology and properties of the human blood vessels to integrate multiple organ-on-chips. Specifically, we present two templating strategies to fabricate hollow PDMS tubes with adjustable diameters and wall thicknesses, where metal rods or airflow were employed as the inner templates, while plastic tubes were used as the outer template. The PDMS tubes could then be functionalized by human umbilical vein endothelial cells (HUVECs) in their interior surfaces to further construct the elastomeric biomimetic blood vessels. The endothelium developed biofunctionality as demonstrated by the expression of endothelial biomarker CD31 as well as dose-dependent responses in the secretion of von Willebrand factor and nitric oxide upon treatment with pharmaceutical compounds. We believe that, with their clear advantages including high optical transparency, gas permeability, and tunable elasticity matching those of native blood vessels, these free-form PDMS vascular modules can supplement the bulk vascular organoids and likely replace the inert plastic tubes in integrating multiple organoids into a single microfluidic circuitry.